Strengths within the Community Perceived by Older Adults Living Alone in a Semi-Mountainous Rural Region: A Qualitative Study - Ai Nakai; Ikuharu Morioka (MDPI AG, 2024)
It is recommended that health promotion activities in the community focus on residents' strengths. Hence, this study explored the community strengths perceived by older adults living alone in a semi-mountainous rural region of Japan. A qualitative, descriptive approach was used. Content analysis was performed using data obtained through face-to-face interviews. Interview data were coded; codes were classified based on similarity to create subcategories and categories. The strengths within the community, as perceived by older adults living alone in a semi-mountainous rural region, were revealed in four categories related to ten subcategories: "loose connections with others", "active community participation", "close relationships with community professionals", and "familiarity with the living environment". Strengths within the community perceived by older adults living alone in a semi-mountainous rural region were cultivated in an environment formed by their past lives. Utilizing these resources may help support community-based societies in semi-mountainous rural regions where depopulation and aging are expected to continue in the future. This study was not registered.